Efficacy and safety of the RTS,S/AS01 malaria vaccine during 18 months after vaccination: a phase 3 randomized, controlled trial in children and young infants at 11 African sites. - RTS,S Clinical Trials Partnership (Public Library of Science (PLoS), 2014)
Background A malaria vaccine could be an important addition to current control strategies. We report the safety and vaccine efficacy (VE) of the RTS,S/AS01 vaccine during 18 mo following vaccination at 11 African sites with varying malaria transmission. Methods and findings 6,537 infants aged 6-12 wk and 8,923 children aged 5-17 mo were randomized to receive three doses of RTS,S/AS01 or comparator vaccine. VE against clinical malaria in children during the 18 mo after vaccine dose 3 (per protocol) was 46% (95% CI 42% to 50%) (range 40% to 77%; VE, p<0.01 across all sites). VE during the 20 mo after vaccine dose 1 (intention to treat [ITT]) was 45% (95% CI 41% to 49%). VE against severe malaria, malaria hospitalization, and all-cause hospitalization was 34% (95% CI 15% to 48%), 41% (95% CI 30% to 50%), and 19% (95% CI 11% to 27%), respectively (ITT). VE against clinical malaria in infants was 27% (95% CI 20% to 32%, per protocol; 27% [95% CI 21% to 33%], ITT), with no significant protection against severe malaria, malaria hospitalization, or all-cause hospitalization. Post-vaccination anti-circumsporozoite antibody geometric mean titer varied from 348 to 787 EU/ml across sites in children and from 117 to 335 EU/ml in infants (per protocol). VE waned over time in both age categories (Schoenfeld residuals p<0.001). The number of clinical and severe malaria cases averted per 1,000 children vaccinated ranged across sites from 37 to 2,365 and from -1 to 49, respectively; corresponding ranges among infants were -10 to 1,402 and -13 to 37, respectively (ITT). Meningitis was reported as a serious adverse event in 16/5,949 and 1/2,974 children and in 9/4,358 and 3/2,179 infants in the RTS,S/AS01 and control groups, respectively. Conclusions RTS,S/AS01 prevented many cases of clinical and severe malaria over the 18 mo after vaccine dose 3, with the highest impact in areas with the greatest malaria incidence. VE was higher in children than in infants, but even at modest levels of VE, the number of malaria cases averted was substantial. RTS,S/AS01 could be an important addition to current malaria control in Africa. Trial registration www.ClinicalTrials.gov NCT00866619 Please see later in the article for the Editors' Summary.